RTVE’s transmedia strategy aimed at young audiences: the case of Playz (2017-2020) - Gaizka Eguzkitza-Mestraitua; Miguel-Ángel Casado-del-Río; Josep-Àngel Guimerá-i-Orts (Communication & Society (Formerly Comunicación y Sociedad), 2023)
Generally speaking, audio-visual consumption is changing. More specifically, in recent years young people have increased their viewing of content through the Internet, which is often supplied through online platforms. This article focuses on one the Playz platform, which is one of the key strategies being used by Spanish public television (RTVE), as it aims to reconnect with the new generations through transmedia narratives. Based on studies undertaken by Costa Sánchez (2013) and Cascajosa-Virino (2018), a content analysis of the series broadcast on Playz between 2017 and 2020 has been carried out, taking into account the duration, year of release, and number of episodes or seasons for each of them. This study confirms a clear interest by this platform in generating products that are innovative from their very conception. In fact, a large number of transmedia strategies have been identified, such as episodes turned into films, a high degree of interactivity with the audience, original music videos, promotional events and more, which is in line with Playz’s public service obligation to reach out to all types of audiences through all the platforms available to them.